Benign recurrent intrahepatic cholestasis – case series and literature review (Indian Journal of Case Reports, 2024)
Benign recurrent intrahepatic cholestasis (BRIC) is a rare form of intrahepatic cholestasis seen in patients with genetic predispositions. It is a rare disease of unknown prevalence and is transmitted as an autosomal recessive pattern of inheritance. The available literature for BRIC is limited. It is hard to formulate the true prevalence of the disorder. Often precipitated by a trigger like viral infections and drugs, this condition results in a self-limiting episode of cholestasis. We present a case series of three patients with the clinical picture of BRIC. All three cases were fully evaluated for the cause of cholestasis and thereafter treated with ursodeoxycholic acid and rifampicin, which showed complete recovery.